Collaborative Governance Pengembangan Destinasi Wisata Pada Perkampungan Budaya Betawi Setu Babakan Provinsi DKI Jak - YS, Mulyanto; Sri Rahayu, Neneng (Family Welfare Education, 2025)
This research on Collaborative Governance for Tourism Development at the Betawi Cultural Village of Setu Babakan in DKI Jakarta aims to explore the collaborative dynamics within this cultural tourism destination. Effective management and promotion of Setu Babakan rely on structured collaboration among various stakeholders, including government institutions, local communities, SMEs, cultural leaders, media, universities, and the private sector, all of whom play crucial roles in sustaining this heritage site. Using a qualitative descriptive method with a case study approach, the research seeks a deep understanding of the factors influencing the application of collaborative governance in tourism development. Based on Emerson and Nabatchi's (2015) Collaborative Governance Regime, which stresses the need for long-term participatory systems and flexible, horizontal stakeholder relationships, the study reveals significant gaps in collaboration. Key influences on Setu Babakan's development include diverse tourist attractions, planning documentation needs, community engagement, infrastructure, and promotion efforts. The findings indicate that, while Betawi culture is a core asset, stakeholder collaboration remains informal, with limited dialogue and no formal framework, such as MoUs or detailed SOPs, to guide the interactions. Challenges include the need for structured mediation and clearer roles within a collaborative framework. The study recommends establishing formal agreements, forming collaborative work teams, and creating digital communication platforms to strengthen coordination and improve economic outcomes. Expected results include enhanced decision-making, stronger stakeholder relationships, and optimized digital tools to promote Setu Babakan